Impact of Edoxaban on Thrombin-Dependent Platelet Aggregation. (14th October 2020) - Sokol, Juraj; Nehaj, Frantisek; Ivankova, Jela; Mokan, Michal; Lisa, Lenka; Zolkova, Jana; Vadelova, Lubica; Mokan, Marian; Stasko, Jan
Edoxaban, a direct factor Xa inhibitor (FXa), is the fourth direct oral anticoagulant (DOAC) approved for clinical use. As the main adverse event is bleeding, it is relevant whether edoxaban has additional effects on platelet function. We aimed to assess in vitro aggregation in patients with atrial fibrillation (AF) receiving edoxaban. We evaluated 20 AF patients treated with edoxaban. We assessed light transmittance platelet aggregation (LTA) with 100 nmol/L γ-thrombin. The LTA was performed at 2 time-points. The thrombin-induced platelet aggregation was significantly lower 2 hours after edoxaban was taken compared to baseline measurement (27.25% ± 30.8% vs. 60.35% ± 33.3%). In addition, we also performed 16 subanalyses in order to identify the differences in the outcome of different comorbidities, age, dosage, liver and kidney function tests, and concomitant treatment. Results of the subgroup analyses were consistent with the findings of the main analysis; there was no apparent heterogeneity across the prespecified subgroups. The thrombin-induced platelet aggregation is reduced in non-valvular AF patients receiving edoxaban.